Assembling Two‐Phase Enzymatic Cascade Pathways in Pickering Emulsion. Issue 7 (13th March 2019) - Pan, Yongchun; Qiu, Wu; Li, Qin; Zhu, Shuihong; Lin, Changxu; Zeng, Wenbin; Xiong, Xueqing; Liu, Xiang Yang; Lin, Youhui
Abstract: The design of enzymatic cascade pathways in biphasic systems with high efficiency is still a big challenge. Herein, we report a simple and efficient strategy for one‐pot biphasic tandem reactions by positioning distinct biocatalysts in spatially separate domains of Pickering emulsion. Due to the large interfacial area and the stability of Pickering interfacial biocatalysts, the as‐obtained Pickering emulsion system was confirmed as a nice microreactor with highly enhanced catalytic performance. Furthermore, in this hybrid catalytic system, unconventional computing relied on enzymatic cascade reactions can be performed. Such Pickering emulsion‐based logic system offers several distinctive advantages, including less "cross‐talk" and signal amplification. We believe that our result will have critical applications in future biocatalysis, nanomachines, smart diagnostics, intelligent drug delivery, nanomechanical, and electronics. Abstract : Two‐Faced : With the aid of Pickering Emulsion, enzymatic interfacial catalysis and two‐phase cascade pathways for a logic network are presented. The results will have critical applications in future biocatalysis, nanomachines, smart diagnostics, intelligent drug delivery, nanomechanical, and electronics.